Evaluation of the Perception of a University Group of Teachers about Education as a Social Phenomenon in Colombia - Moreno-Collazos, Jorge Enrique (2016)
Objective: This paper aims to evaluate the perception of a university group of teachers about education as a social phenomenon. An analytical cross-sectional study was conducted with a group of university teachers in Bogota, Colombia, in October 2014. A survey was applied in order to evaluate the perception about education as a social phenomenon; the data analysis was performed using SPSS software version 19. The population studied consisted of 60 university professors with an average age of 42.2 ± 14.4 years, and with 6.15 years of teaching practice. Male gender was predominant with 53% (n = 32). There were statistically significant differences in the results related to the concept of education (p = 0.05 to 0.00) and to the following items: “Do you consider that investment in public education is enough?” (p = 0.02), “Is education a political model?” (P = 0.03); in aggregate age, “Is access to higher education conceived by the Colombian government with social concern?”, “Does the environment influence the Colombian student’s education development?” (p = 0.02 to 0.00); it was the same case for the interpretive sociology for the item “Are patterns of educational assessment adequate in the country?” (p = 0.04). In conclusion, it was found that there are differences in teachers’ conceptions about the construction of education as a social phenomenon.f education as a social phenomenon by finding differences between the conceptions of it in teaching.